Validating clinical characteristics of primary failure of eruption (PFE) associated with PTH1R variants - Cristina Grippaudo; Isabella D'Apolito; Concetta Cafiero; Agnese Re; Pietro Chiurazzi; Sylvia A. Frazier-Bowers (SpringerOpen, 2021)
Abstract Background Primary failure of eruption (PFE) is a hereditary condition, and linkage with variants in the PTH1R gene has been demonstrated in many cases. The clinical severity and expression of PFE is variable, and the genotype-phenotype correlation remains elusive. Further, the similarity between some eruption disorders that are not associated with PTH1R alterations is striking. To better understand the genotype-phenotype correlation, we examined the relationship between the eruption phenotype and PTH1R genotype in 44 patients with suspected PFE and 27 unaffected relatives. Sanger sequencing was employed to analyze carefully selected PFE patients. Potential pathogenicity of variants was evaluated against multiple genetic databases for function prediction and frequency information. Results Mutational analysis of the PTH1R coding sequence revealed 14 different variants in 38 individuals (30 patients and 8 first-degree relatives), 9 exonic and 5 intronic. Their pathogenicity has been reported and compared with the number and severity of clinical signs. In 72.7% of patients with pathogenic variants, five clinical and radiographic criteria have been found: involvement of posterior teeth, involvement of the distal teeth to the most mesial affected, supracrestal presentation, altered vertical growth of the alveolar process and posterior open-bite. In cases with mixed dentition (3), the deciduous molars of the affected quadrant were infraoccluded. Discussion The probability of an affected patient having a PTH1R variant is greater when five specific clinical characteristics are present. The likelihood of an eruption defect in the absence of specific clinical characteristics is rarely associated with a PTH1R mutation. Conclusions We report here that systematic clinical and radiographic observation using a diagnostic rubric is highly valuable in confirming PFE and offers a reliable alternative for accurate diagnosis.